2021
DOI: 10.1177/21650799211037528
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Efficacy and Acceptability of an Online Exercise and Nutrition Workplace Wellness Program: A Brief Report

Abstract: Background Workplace wellness programs (WWP) offer physiological and psychological benefits to employees and financial and productivity benefits to employers. However, the COVID-19 pandemic has prevented in-person sessions and has required WWP’s to transition to online platforms. The purpose of this brief report was to assess the preliminary feasibility, acceptability, and efficacy of a mobile version of the Bruin Health Improvement Program (BHIP mobile) WWP. Methods Participants virtually attended (i.e., via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Second, researchers have increasingly examined the effectiveness of digital WHP programs (see, e.g. SantaBarbara et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, researchers have increasingly examined the effectiveness of digital WHP programs (see, e.g. SantaBarbara et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Second, researchers have increasingly examined the effectiveness of digital WHP programs (see, e.g. SantaBarbara et al, 2022). For example, for sports offerings, mobile platforms and online sessions provide flexibility for employees to participate remotely and simultaneously limit the costs for companies in installing onsite training locations (SantaBarbara et al, 2022).…”
Section: Ijwhm 172mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of intervention studies on fall prevention in the community-dwelling older population reported a withdrawal rate of 9.1%-16% and a participation rate of over 80% after a 2-3-month intervention period (Nyman et al, 2012). Moreover, a previous study conducting online interactive exercise sessions for adults aged 25-58 years reported a withdrawal rate of 50% (Santabarbara et al, 2022). An online intervention study of cancer patients an average age of 65 years, reported participation rates of 80% for one-on-one online sessions and 29% for group-based programs (Dennett et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mobile health technology, including wearable activity trackers and smartwatches, might effectively engage shift workers in wellness programs [ 12 ]. Since the COVID-19 pandemic has caused us to adjust to life indoors, efforts to reduce the spread of the virus have forced people to adapt to online exercise using Zoom, Instagram, and YouTube [ 14 ]. As various wearable tracking devices and smartwatches have been developed, which can positively influence health behaviors, such as increasing physical activity, research on mobile wellness programs to promote physical activity has been actively conducted [ 15 ].…”
Section: Introductionmentioning
confidence: 99%